Blind multiuser detection based on instantaneous mixtures - ZHAO Chen; GOU Bin; WANG Ke (Tongxin xuebao)
A blind multiuser detection technique used in multiple-input multiple-output orthogonal frequency division multiplexing （MIMO-OFDM） systems was proposed. The basic thought is to apply the existing blind source separation （BSS） algorithm to the signal detection in MIMO-OFDM systems. From the viewpoint of frequency bin （FB）, the pro- posed method resolves the application problem of BSS algorithm in the systems with delay. In the meanwhile, the prob- lem of permutation indeterminacy which is brought by the recomposition from separated signals and the problem of the complex scaling indeterminacy caused by the complex signal nature in communication systems are also settled by it. Theoretical analysis and computer simulation confirm that the proposed method is valid.